A Wish List for the Advancement of University and College Counseling Centers. Issue 1 (2nd January 2016) - Bishop, John B.
ABSTRACT: University and college counseling centers continue to meet emerging challenges in higher education. This article addresses three issues: the need for a more unified organizational structure to represent the profession, the potential value for counseling centers in seeking accreditation, and the importance of specialized training for those entering this professional field.